2007
DOI: 10.1111/j.1525-1438.2006.00778.x
|View full text |Cite
|
Sign up to set email alerts
|

F-18 fluorodeoxyglucose uptake in leiomyomatous uterus

Abstract: Leiomyomas of uterus are common disease in gynecology. It is important to differentiate leiomyoma from leiomyosarcoma at the decision of treatment methods, especially in the case of the conservative treatment for uterine leiomyoma. But the exact diagnosis of benign leiomyoma is often difficult due to the degeneration of myoma by imaging modalities including magnetic resonance imaging. Recently, whole-body positron emission tomography (PET) using F-18 fluorodeoxyglucose (FDG) has been used for a diagnosis of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…In addition, FDG uptake in uterine leiomyoma declines with age [37]. But there are some case reports of intense FDG uptake in large or degenerated benign leiomyomas [36,[38][39][40][41]. Reported high uptake in the leiomyomas might be owing to increased vascularity [40] or large sizes of the tumors [41].…”
Section: Endometrial Uptakementioning
confidence: 91%
See 1 more Smart Citation
“…In addition, FDG uptake in uterine leiomyoma declines with age [37]. But there are some case reports of intense FDG uptake in large or degenerated benign leiomyomas [36,[38][39][40][41]. Reported high uptake in the leiomyomas might be owing to increased vascularity [40] or large sizes of the tumors [41].…”
Section: Endometrial Uptakementioning
confidence: 91%
“…Therefore, nonmenstrual-related endometrial uptake may represent either benign or malignant process. MRI correlation is usually helpful for differentiation [39,40].…”
Section: Endometrial Uptakementioning
confidence: 99%
“…In general, SUV values for leiomyosarcoma were observed to be significantly greater than those for leiomyoma. However, numerous reports for 18-FDG-avid leiomyoma were also identified (36)(37)(38). Furthermore, a series of comprehensive analyses for those patients who underwent 18-FDG-PET/CT revealed that small proportion of benign uterine leiomyomas exhibited positive 18-FDG uptake.…”
Section: Discussionmentioning
confidence: 99%
“…We have already reported on the usefulness of FDG-PET for the diagnosis of uterine sarcomas (7)(8)(9). However, several studies (10,11) have shown positive results for FDG-PET in cases of LM, and its usefulness in the differential diagnosis of LM and LMS is unclear.…”
Section: Introductionmentioning
confidence: 99%